Changes in Pediatric Spine Surgery Patterns Over the Last 10 Years Among ABOS Part II Candidates. Issue 18 (15th September 2019) - Nielsen, Ena; Andras, Lindsay M.; Hosseinzadeh, Pooya; Mignemi, Megan; Sawyer, Jeffrey R.; Flynn, John M.; Albanese, Stephen; Skaggs, David L.
Abstract : Study Design: A retrospective review of prospectively collected data. Objective: Our purpose was to evaluate the volume of pediatric spine cases being done by surgeons applying for American Board of Orthopaedic Surgeons (ABOS) certification. Summary of Background Data: Pediatric orthopedic surgery has become increasingly subspecialized over the past decade. Methods: Data were reviewed from the ABOS for surgeons undergoing part II of ABOS certification between 2004 and 2014. Applicants were divided into pediatric orthopedic surgeons and spine surgeons based on their self-declared subspecialty for the ABOS Part II examination. A total of 102, 424 cases were reviewed to identify spine cases performed on patients <18 years old. Results: Between 2004 and 2014, the total number of ABOS part II pediatric candidates increased significantly, from a low of 15 to a high of 44 ( r 2  = 0.68, P  = 0.001). During this time frame, there has been no significant increase in the total number of pediatric spine cases reported ( r 2  = 0.09, P  = 0.19). In 2004, 46.5% (33/71) of the pediatric spine cases were done by spine surgeons, which decreased to 17.3% (28/162) in 2014. Conversely in 2004, 53.5% (38/71) of pediatric spine cases were done by pediatric orthopedists, which increased to 82.7% (134/162) in 2014. The number of pediatric candidates performing pediatric spine cases decreased 35% from 2004 to 2014, but the percentage performing >20 spine cases during their candidate year has increased from 0% to 7% ( r 2  = 0.31, P  = 0.04). Conclusion: The share of pediatric spine surgeries performed by pediatric candidates has increased from 54% in 2004 to 83%, with a corresponding fall in the share surgeries performed by spine candidates (47% to >17%). The percentage of pediatric candidates performing more than 20 spine cases/year increased from 0% to 7%, reflecting a trend of spine subspecialization within pediatric surgery. Level of Evidence: 3 Abstract : From 2004 to 2014, the percentage of pediatric spine surgery done by ABOS part II pediatric orthopedic surgeon candidates increased, while the percentage done by spine surgeon candidates decreased. A smaller percentage of pediatric candidates report performing a higher volume of spine surgery, suggesting a trend of more subspecialization in pediatric surgery.